1986
DOI: 10.1056/nejm198612043152303
|View full text |Cite
|
Sign up to set email alerts
|

Positive Response to Edrophonium in Patients with Neurotoxic Envenoming by Cobras (Naja naja philippinensis)

Abstract: To study the ability of anticholinesterase drugs to reverse the potentially fatal paralytic effects of cobra venom, we conducted a placebo-controlled, double-blind crossover trial of intravenous edrophonium (Tensilon) in 10 adults with neurotoxic envenoming caused by bites of the Philippine cobra (Naja naja philippinensis). There was significantly more improvement in ptosis and endurance of upward gaze after edrophonium than after placebo. Five minutes after injection, the mean difference (+/- SD) in the perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 14 publications
1
51
0
2
Order By: Relevance
“…Improvement in neurological signs was not seen until 24 hours after antivenom administration. Ancillary treatment has been recommended with anti-cholinesterase drugs; Edrophonium Chloride could benefit those patients bitten by a coral snake with postsynaptic neurotoxic venom 41 , and neostigmine had demonstrated the potential to reverse neuroparalysis 9,39 . Even when used in several occasions in clinical practice, no standard protocol has been followed.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in neurological signs was not seen until 24 hours after antivenom administration. Ancillary treatment has been recommended with anti-cholinesterase drugs; Edrophonium Chloride could benefit those patients bitten by a coral snake with postsynaptic neurotoxic venom 41 , and neostigmine had demonstrated the potential to reverse neuroparalysis 9,39 . Even when used in several occasions in clinical practice, no standard protocol has been followed.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial involving Naja naja philippinensis bites 34 has shown the effectiveness of anticholinesterase drugs in treating elapid envenoming with severe paralysis caused by a predominantly or exclusively postsynaptic action at the neuromuscular junction. A favorable response to neostigmine in three cases has also been observed in Brazil, two of which were attended a considerable time after being bitten 8,32 .…”
Section: Discussionmentioning
confidence: 99%
“…In one of our cases, which did not respond to anticholinesterase drugs, the offending species may have been M. corallinus, which venom acts presynaptically blocking the release of acetylcholine from nerve endings at the neuromuscular junction 17,31 . However, the effect of neostigmine is always temporary 8,32,34 , and complete reversal of postsynaptic neurotoxicity can be achieved only with antivenom.…”
Section: Discussionmentioning
confidence: 99%
“…sPLA2s are also some of the most pharmacologically active, multi-effect (neuro-myo-cyto-hemotoxic) venom components ( While sPLA2 inhibition might prove sufficient as a "bridge-to-survival" for many types of venoms when administered in a pre-referral setting and, at times, be sufficient for treatment, future SMTs might be mixtures of other SMT (Figure 3a). Some targets could also be inhibited indirectly by SMTs, such as three-finger toxins, whose effects might sometimes be mitigated by acetylcholinesterase inhibitors, though the use of these inhibitors remains controversial despite decades of use for this purpose [52,61,[64][65][66]. In addition, SMTs might be used to slow the spread of venom by paralyzing lymphatic smooth muscles (e.g., with lignocaine) [67].…”
Section: Venom Target Selectionmentioning
confidence: 99%
“…In 1972, Banerjee et al presented an early example of repurposing an SMT for snakebite when neostigmine was used to treat the paralytic effects of an elapid bite [52]. Multiple groups have since investigated the use of this class of acetylcholinesterase inhibitors in the clinical setting with variable results [52,61,65,66]. Development of a hypothetical SMT using a repurposing pathway are shown in Figure 4.…”
Section: Repurposing As a Strategy For Discovery And Developmentmentioning
confidence: 99%